Pembelajaran Maharatul Kalam Dalam Perspektif Scientifik Approach - Sofiatus Sobriyah (LP3M KH Yazid Karimullah Institute, 2022)
The scientific approach is the essence of the 2013 curriculum which defines the Graduate Competency Standards (SKL), in accordance with the Minister of Education and Culture concerning the education curriculum. The principle of preparing the K13 curriculum refers to Article 36 of Law no. 20 of 2003, which says that the preparation of the curriculum must pay attention to increasing faith, morals, self-management, art and national values. In line with the development and growth of education that continues to advance, madrasas improve the quality of schools including the process of skills, learning processes and achievements obtained by schools and madrasa students so that learning at Madrasah Aliyah Negeri 1 Jember applies a scientific approach until now. This article describes in detail about how to apply the scientific approach at Madrasah Aliyah Negeri 1 Jember and the supporting and inhibiting factors for the success of Maharatul Kalam learning in the scientific approach perspective. The type of research used is field research. The data collected by the author through primary data includes data from interviews and observations regarding the application of the scientific approach in learning Maharatul Kalam at Madrasah Aliyah Negeri 1 Jember, while secondary data includes literature review or documentation. The data obtained will be processed and analyzed by means of data reduction, data display and drawing conclusions. The results showed that the application of a scientific approach in learning Maharatul Kalam contained supporting and inhibiting factors. This can be seen from the application of the 5 components of the scientific approach which include: (a) observing (observing), (b) asking (questioning), (c) exploration (experimenting), (d) association (reasoning), (e) communicating (networking). ). However, the application of the scientific approach requires carrying capacity in the form of facilities and infrastructure for teacher and student handbooks, the presence of accompanying teachers and teachers who become instructors of the 2013 curriculum, as well as the existence of curriculum training activities carried out by schools and in the application of the scientific approach the inhibiting factor is the problem. students who do not have an Arabic educational background and are not fluent in reading the Koran.